The Role of Mediating effects of User Satisfaction and Behavioural Intention on the Influence of the e-Tax System on Tax Compliance Behaviour: An application of Bootstrapping Technique - Faustine Juma Masunga; Harun Jeremia Mapesa; Andwilile Nyalle Mwakibete; Moshi James Derefa; Jema Edmund Myava; Joseph Simon Kiria (Universitas Airlangga, 2021)
The purpose of this study was premised on the role of mediating effects of user satisfaction and behavioural intention on the influence of the quality of the e-tax system on tax compliance behaviour. A mixed-methods approach (sequential explanatory design) was applied where the qualitative findings were used to supplement the results from the quantitative findings. A PLS-SEM technique with SmartPLS 3 was used to analyse data quantitatively while the qualitative data were analyzed using thematic analysis. The results revealed that behavioural intention mediates only the relationship between information quality and tax compliance behaviour. When multiple mediators are used (behavioural intention and user satisfaction) the findings unveiled that service quality and system quality have a significant positive indirect effect on tax compliance behaviour.